Investigation studies on mechanical properties of PH15-5 stainless steel for selective laser melting - Tan, Wei Jie (2019)
Additive manufacturing (AM) is an innovative technology which has been present in recent years. AM is a transformative method to industrial production and in the right applications, it delivers a perfect combination of improved performance, complex geometries and simplified fabrications in terms of its efficiency. There are seven categories of AM processes: VAT photopolymerisation, binder jetting, sheet lamination, material jetting, material extrusion, directed energy deposition and powder bed fusion. In this final year project, the focus would be on the powder bed fusion category using the selective laser melting (SLM) process. SLM is used to produce metal objects using powders. In this study, PH15-5 stainless steel was used as the investigative material. This study is done to develop a set of optimised parameters for SLM. The different sets of parameters will be used to conduct the investigation. Further analysis of the mechanical experiments and fracture analysis will be done in this study. From the density tests, when using the high laser power (380 W), it was found that the best relative density achieved was 99.36% using 100µm hatch spacing, 380W laser power. On the other hand, when using the low laser power, the best relative density achieved was 99.77% using a hatch spacing of 160µm and a lower laser power of 140W. From the roughness test, the smoothest surfaces were obtained using a high laser power of 380W, 130µm and at a lower laser power of 140W with hatch spacing of 150µm. The best average roughness value for the high laser power samples was 7.23µm and for the low laser power samples, it was 7.21µm. The highest hardness value obtained at a higher laser power of 380W was when using a hatch spacing of 80µm, with a hardness value of 317.3HV. The highest hardness value obtained at iv lower laser power of 140W was when using a hatch spacing of 80µm with a hardness value of 286.6HV. From the tensile test, the tensile coupon samples which achieved the best tensile properties were HP3, LP8 and HP1.